Burnout and Its Association With Competence Among Dental Interns in China - Liu, Yingjun; Song, Yi; Jiang, Yong; Guo, Chuanbin; Zhou, Yongsheng; Li, Tiejun; Ge, Wenshu; An, Na (Frontiers in Psychology, 2022)
Intern physicians are generally more burdened by stress than the general population. This cross-sectional study aimed to assess the potential correlation between burnout and self-evaluation of competency among dental interns. A self-administered anonymous survey was conducted on 91 dental interns in the Peking University School of Stomatology, from August 2019 to June 2020. It consisted of a psychological stress questionnaire, including burnout (MBI-HSS) and self-evaluation of clinical competence. The Wilcoxon signed rank test was used to determine the differences between self-evaluation scores of clinical competence. Results showed average scores for emotional exhaustion, depersonalization, and personal accomplishment of 22.22 ± 9.04, 8.16 ± 5.21, and 36.08 ± 7.76, respectively. Dental clinical technology was considered more useful than other clinical competencies, and there was a correlation between its importance and the stress caused by its deficiency (r = -0.201, p = 0.056). Significant associations were found between stress due to a lack of dental clinical technology and high emotional exhaustion (r = 0.273, p < .05). Burnout was common among the dental interns, which may be a valuable finding. Among the six different aspects of clinical competence, “dental clinical technology” represented the most stressful item. Strengthening pre-clinical training and promptly conducting targeted training in the early clinical process may be considered as decompression measures.